Oranges are not the only fruit - Winterson, Jeanette, 1959- (Vintage, 1996)
This is the story of Jeanette, adopted and brought up by her mother as one of God's elect. Zealous and passionate, she seems seems destined for life as a missionary, but then she falls for one of her converts.